Pengaruh Kualitas Sistem dan Informasi Dalam Pendidikan Akuntansi - Aditya Pradina Hermawan; Aprina Nugrahesthy Sulistya Hapsari (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2021)
This research aims to examine the effect of system quality, information quality, user satisfaction, and the net benefits of using information systems in accounting learning. Data in this research were obtained by distributing questionnaires with a sample of 70 students Accounting Study Program. This research is a descriptive quantitative study and uses multiple linear regression analysis. The results showed that system quality and information quality had a positive effect on user satisfaction, and information quality and user satisfaction had a positive effect on net benefits, but system quality did not affect net benefits. The results of this study can be used as consideration in making improvements related to the implementation and use of the f-learn in accounting learning and education.